Advances in the Involvement of Gut Microbiota in Pathophysiology of NAFLD - Jiang, Xiaofan; Zheng, Juan; Zhang, Shixiu; Wang, Baozhen; Wu, Chaodong; Guo, Xin (Frontiers in Medicine, 2020)
Non-alcoholic fatty liver disease (NAFLD) is characterized by hepatic steatosis and progresses to non-steatohepatitis (NASH) when the liver displays overt inflammatory damage. Increasing evidence has implicated critical roles for dysbiosis and microbiota-host interactions in NAFLD pathophysiology. In particular, microbiota alter intestine absorption of nutrients and intestine permeability, whose dysregulation enhances the delivery of nutrients, endotoxin, and microbiota metabolites to the liver and exacerbates hepatic fat deposition and inflammation. While how altered composition of gut microbiota attributes to NAFLD remains to be elucidated, microbiota metabolites are shown to be involved in the regulation of hepatocyte fat metabolism and liver inflammatory responses. In addition, intestinal microbes and circadian coordinately adjust metabolic regulation in different stages of life. During aging, altered composition of gut microbiota, along with circadian clock dysregulation, appears to contribute to increased incidence and/or severity of NAFLD.